The Quality of The Public Service At the Civil Registry Service Office of Bima District - Rosnani, Rosnani; Bahri, Syamsul; Juharni, Juharni (Universitas Negeri Makassar, 2021)
This study aims to examine, analyze and interpret: The implementation of public services at the Department of Population and Civil Registration in Bima Regency. Because if you look at the current phenomenon, there are still many complaints from the community, such as lack of human resources, lack of socialization, limited facilities. This research is descriptive analysis using a qualitative approach, the data obtained from a number of informants. The results of the study indicate that the services provided by the Population and Civil Registration Office of Bima Regency are effective, timely and systematic. by online. Through innovation and sufficient work ethic, innovations are created such as: servant services to the people's porch for the issuance of population cards and civil registration that are fast, free, free of charge with mobile service cars to support technology-based services in improving quality performance. The conclusion of the researcher, 1) The implementation of services organized by the Department of Population and Civil Registration of Bima Regency provides public services in accordance with the needs of the community. in document-making services 2) Improving the quality of public service performance carried out by the Department of Population and Civil Registration of Bima Regency with regulations that bind the necessity that the quality of public service performance will be achieved optimally.